Errors on EFL Students’ Paragraph Writings - Sulaiman Masagus; Indawan Syahri (International Journal of English and Applied Linguistics (IJEAL), 2022)
It is common for EFL students to commit grammatical errors in the early stage of learning writing, especially in paragraph writing. Therefore, this research aimed to identify the types of errors and the most dominant ones committed in descriptive paragraph writing exercises. A qualitative research design was applied to this study. Writing exercises were used as research instruments to collect the data. Twenty-six students of the English Study Program were used as participants in this study. Error Analysis Method (EAM) based on Surface Structure Taxonomy and percentage error analysis was used to analyze the data. The findings showed that there were four types of errors committed referring to misformation with a frequency of error was 47 (0,14 %), omission with a frequency of error 81 (0,24%), misordering with a frequency of error 153 (0,47%), and addition with the frequency of error was 45 (0,13%). In this case, a misordering mistake was the dominant one, and an addition error was the least dominant one committed by the students. In conclusion, the researchers assume that some factors affect students' mistakes, such as lack of knowledge and competence in English grammar. The error analysis method was a very suitable way to identify types of errors using simple present tense in descriptive paragraph writing.